TOEFL Basic Skills Training for Students at State Islamic University of Bandung - Ridwan, Revi Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service aims to improve basic TOEFL skills for State Islamic University of Bandung through structured training. This program is carried out through several stages, preparation, implementation, independent training, and evaluation. At the preparation stage, a need analysis is carried out to prepare relevant training materials, followed by the formation of an implementation team and recruitment of participants. The implementation of the training includes the delivery of material on the TOEFL format, question strategies, and practice through intensive training. Participants were also given modules to support independent training to strengthen their understanding and abilities individually. In the evaluation stage, a TOEFL test simulation is used to assess the improvement of participants' abilities, which are then analyzed and discussed in discussion sessions to provide feedback and suggestions for improvement. The results of the program show that this training has succeeded in increasing students' understanding, skills, and confidence in facing the TOEFL test. This program also creates awareness of the importance of English mastery for academic and professional needs, as well as making a positive contribution to the development of student competencies